One-pot catalytic conversion of glucose to 2,5-furandicarboxylic acid over NiO-modified ZSM-5 zeolites: Effects of reaction temperature and solvent ratio - Pratama, Arnia Putri; Mulyadi, Andita Junia; Wibowo, Rahmat; Krisnandi, Yuni Krisyuningsih (Environmental and Materials, 2025)
Background: 2,5-Furandicarboxylic acid (FDCA) has gained increasing attention as a key bio-based intermediate for the production of polyethylene furanoate (PEF) and other sustainable polyesters, offering a viable alternative to fossil-derived monomers. Although FDCA is conventionally produced via oxidation of 5-hydroxymethylfurfural (HMF), direct one-pot conversion of glucose remains challenging due to the requirement for integrated catalytic functions and the strong influence of reaction conditions. Hierarchical zeolites modified with transition-metal oxides are promising for one-pot glucose-to-FDCA conversion; however, the effects of reaction temperature and solvent composition have not been systematically evaluated and are examined here using hierarchical ZSM-5, NiO-modified ZSM-5, and NiO catalysts. Methods: Hierarchical ZSM-5 was synthesized via a dual-template method and modified with NiO through an impregnation–spray technique to introduce redox-active sites. The catalysts were characterized using X-ray diffraction, Fourier-transform infrared spectroscopy, nitrogen physisorption, and Scanning Electron Microscope-Energy Dispersive X-Ray to establish correlations between structural, compositional, and textural properties and catalytic performance. Catalytic reactions were conducted at varying temperatures using a γ-valerolactone–water solvent system with different volume ratios. Findings: NiO-modified hierarchical ZSM-5 exhibited superior catalytic performance compared to the parent zeolite and NiO, achieving a maximum FDCA yield of 2.36% at 150 °C with an optimal γ-valerolactone–water ratio of 1:1. Higher FDCA yield over NiO-modified hierarchical ZSM-5 reflects the combined effects of hierarchical porosity, NiO species, reaction temperature, and solvent ratio. Conclusion: This study demonstrates that NiO-modified hierarchical ZSM-5 can promote one-pot glucose-to-FDCA conversion, with reaction temperature and solvent ratio identified as key parameters for performance optimization. Novelty/Originality of this article: This study provides a systematic assessment of the effects of reaction temperature and γ-valerolactone–water solvent ratio on FDCA formation over NiO-modified hierarchical ZSM-5 in a one-pot glucose conversion system, establishing catalyst and process design principles.